Main and Ratooned Rice Pest Populations in Lowland Rice Fields, South Sumatra Applied Bioinsecticide from Entomopathogens - Lina Budiarti; Siti Herlinda; Suwandi Suwandi; Khodijah Khodijah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
The pests that attack each plant phase also varies. The aimed of this study was to compare the main population of rice insect pests and ratooned in lowland rice field in the vegetative, flowering and milk ripening phase. The main bioinsecticide rice sprayed on rice canopy were comes from the entomopathogenic fungal conidia Metarhizium anisopliae, the entomopathogenic bacterium Bacillus thuringiensis, and as a control area without the application of bioinsecticide or synthetic insecticide. The results showed that population of fake white pests (Cnaphalocrosis medinalis) and white leafhoppers pest (Covana spectra) were more prevalent in vegetative phase rice compared to other types of pests such as green leafhoppers (Nephotettix spp.), Brown leafhoppers (Nilaparvata lugens), zig zag leafhoppers. (Recillia dorsalis), white-back leafhoppers (Sogatella furcifera), grasshoppers, mole cricket (Gryllotalpa gryllotalpa), and yellow rice stem borer (Scirpophaga incertulas). The Leptocorisa acuta and green ladybugs (Nezara viridula) began to attack the flowering and milk ripening phase, which was when the rice was aged about 54-68 days after transplanting (dat). Whereas in ratooned rice, the pest population of L. acuta has appeared on the first observation on rice aged 9 days after harvest (dah) until the ratooned rice was aged 58 days after harvesting. The population of pests was higher in land without bioinsecticide application compared to land applied of bioinsecticides. In ratooned rice, the pest population between the land applied with bioinsecticide M. anisopliae and B. thuringiensis was not significantly different from the land applied by B. thuringiensis which was sold in the market.